Optimizing the Conditions for Whole-Genome Sequencing of Avian Reoviruses - Sonsiray Alvarez Narvaez; Telvin L. Harrell; Olatunde Oluwayinka; Holly S. Sellers; Zubair Khalid; Ruediger Hauck; Erfan U. Chowdhury; Steven J. Conrad (Viruses, 2023)
Whole-genome sequencing (WGS) is becoming an essential tool to characterize the genomes of avian reovirus (ARV), a viral disease of economic significance to poultry producers. The current strategies and procedures used to obtain the complete genome sequences of ARV isolates are not cost-effective because most of the genetic material data resulting from next-generation sequencing belong to the host and cannot be used to assemble the viral genome. The purpose of this study was to develop a workflow to enrich the ARV genomic content in a sample before subjecting it to next-generation sequencing (NGS). Herein, we compare four different ARV purification and enrichment approaches at the virion, RNA and cDNA levels to determine which treatment or treatment combination would provide a higher proportion of ARV-specific reads after WGS. Seven ARV isolates were subjected to different combinations of virion purification via ultracentrifugation in sucrose density gradient or Capto Core 700 resin with or without a subsequent Benzonase treatment, followed by a chicken rRNA depletion step after RNA extraction and a final ARV cDNA amplification step using a single-primer amplification assay. Our results show that the combination of Capto Core 700 resin, Chicken rRNA depletion and cDNA amplification is the most cost-effective strategy to obtain ARV whole genomes after short-read sequencing.